The experience of nurses in care for culturally diverse families: A qualitative meta-synthesis - Saidy Eliana Arias Murcia; Lucero Lopez
Abstract Objective: to understand the experience of nurses in care delivery to culturally diverse families. Method: qualitative meta-synthesis. Exhaustive search in seven databases, three repositories and a manual search in references without time limit, in English, Spanish and Portuguese, resulting in 1609 potentially relevant studies. These were assessed based on the title, summary and full text, determining the final inclusion of 14 studies. Two independent reviewers used the Critical Appraisal Skills Programme (CASP) to assess the quality. The interpretative synthesis implied permanent contrast and consensus among the authors, revealing four categories and one meta-theme. Results: "taking care of a culturally diverse family, the experience of crossing a tightrope". Conclusion: the experience of nurses in care delivery to culturally diverse families is demanding and challenging because it imprints a constant tension among barriers, cultural manifestations and the ethical responsibility of care, incipiently revealing elements of cultural competency. The omission of information in the participants' reports in the studies represents a limitation. The findings offer a baseline for professionals and organizations to focus their intervention efforts on the continuing barriers in care delivery to culturally diverse families and strengthens the need for cultural competency training for nurses.